Pengaruh VAIC terhadap Nilai Perusahaan: Studi pada Perusahaan Farmasi di Bursa Efek Indonesia - Novizar, Amelia (UNIVERSITAS DHARMAWANGSA, 2025)
This study analyzes the effect of the efficiency of intellectual capital management on the value of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. Intellectual capital measurement uses the Value Added Intellectual Coefficient (VAIC) method consisting of VACA, VAHU, and STVA. The value of a company is measured by the Price to Book Value (PBV) ratio. The regression results showed that VACA had a negative and significant effect, VAHU had a positive and significant effect, while STVA had a negative but insignificant effect on the company's value. Simultaneously, the three variables have a significant effect on the company's value. These findings confirm the importance of the role of human resources in creating value in the Indonesian pharmaceutical industry.